Materialy k proektu virtualnyi Muzei Gulaga - Pravozashchitnyi tsentr "Memorial" (Moscow, Russia) (Russia : Memorial, 2004)
Images of collected material, both official and personal for a grand project. The archival records, photographs, drawings, paintings, articles, artifacts, personal belongings and objects were collected and described by a dedicated professional group of historians and artists for a future Gulag Museum.
Keywords: Documentary films